LIFE VALUES OF AMERICAN STUDENTS: HISTORICAL AND PEDAGOGICAL ASPECTS - Ocheretіanуі, Anatolіі (Studies in Comparative Education, 2017)
The article presents the historical and pedagogical aspects of American students’ life values problem. The scientific views of American scientists on the problem of life values are analyzed. The most common is the understanding of life’s values as the foundation on which everyone builds their own life; as the principles of life, which determine how one should behave; as a beliefthat occupies a central posi-tion in the individual’s system of beliefs. In different historical periods, the most im-portant life values of American youth were the ability to intercultural communi-cation, freedom of choice, professional competitiveness, family well-being. American methods of studying terminal and instrumental life values of students in the process of obtaining their education in higher educational institutions have been described. The following main terminal values of American students at the beginning of the twenty-first century are highlighted: the existence of a family, self development, freedom of choice (statements and activities), pluralism and democracy in public relations, patriotism and active social position, professionalism and compete-tiveness, financialsecurity, health and fitness. Attention is drawn to the following functions ofAmerican students’ life values: 1) orientational towards ideals and pat-terns of activity; 2) constructive about life strategies; 3) normative about behavior styles. Curricula and programs of American higher education institutions are aimed at developing the students’life values in the following areas: spiritual, mental, eth-nopsychological, humanistic-communicative, social socialization, socio-political, professional competence and competitiveness, culture of health and safety.